Northern England Serpukhovian (early Namurian) farfield responses to southern hemisphere glaciations - M. H. Stephenson; P. Cózar; M. J. Leng; D. Millward; S. Chenery; L. Angiolini; F. Jadoul (Journal of the Geological Society, 2010)
During the Serpukhovian (early Namurian) icehouse conditions were initiated in the southern emisphere. However, nearfield evidence is inconsistent: glaciation appears to have started in limited areas of eastern Australia in the earliest Serpukhovian, followed by a long interglacial, whereas data from South America and Tibet suggest glaciation throughout the Serpukhovian. New farfield data from the Woodland, Throckley and Rowlands Gill boreholes in northern England allow this inconsistency to be addressed. δ^(18)O from well-preserved late Serpukhovian (late Pendleian to early Arnsbergian) Woodland brachiopods vary between -3.4 and -6.3‰, and δ^(13)C varies between -2.0 and +3.2‰, suggesting a δ^(18)O seawater (w) value of around -1.8‰ VSMOW, and therefore an absence of widespread ice-caps. The organic carbon δ^(13)C upward increasing trend in the Throckley borehole (Serpukhovian to Bashkirian; c. -24 to c. -22‰) and the Rowlands Gill borehole (Serpukhovian; c. -24 to c. -23‰) suggests large-scale burial of organic material, 32 probably in burgeoning lycophyte-dominated coal forest, implying a fall in pCO2. pCO2 reduction appears not to have caused large-scale glaciation until the early Bashkirian, but a scenario of coalescing upland ice-caps through the Serpukhovian with a background of decreasing pCO2 appears to be similar to the process that initiated Cenozoic Antarctic glaciation.